Perancangan Usulan Perbaikan Bagi Restoran Wizzmie Jimbaran Berdasarkan Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Konsumen - Baiq Devi Ariska; I Gusti Ngurah Priambadi; Ni Luh Putu Lilis Sinta Setiawati (GLOBAL SCIENTS PUBLISHER, 2025)
This study discusses the factors that influence consumer purchasing decisions at Wizzmie Jimbaran Restaurant, namely product quality and service quality factors. The purpose of this study is to determine how product quality and service quality influence consumer purchasing decisions. The method used in this study is a quantitative method. The population in this study were consumers who had visited Wizzmie Jimbaran Restaurant from the population, the sample was determined based on research by Hair et al. (2010) sample = number of indicators x 5, then a sample of 80 people was obtained. The data analysis technique used the classical assumption test and hypothesis test with results based on research, product quality and service quality simultaneously had a significant influence on purchasing decisions and all independent variables partially had a significant effect on the dependent variable, but based on the results of the questionnaire, there needed to be a proposal for improvement, namely evaluating recipe standards and portions, attaching visual documentation of dishes, having the right measuring equipment, increasing the number of servers, increasing employee empathy, and providing comfortable facilities for customers waiting.